Low-intensity case management increases contact with primary care in recently released prisoners: A single-blinded, multisite, randomised controlled trial - Kinner, S.; Alati, Rosa; Longo, M.; Spittal, M.; Boyle, F.; Williams, G.; Lennox, N. (BMJ Publishing, 2016)
Background The world prison population is large and growing. Poor health outcomes after release from prison are common, but few programmes to improve health outcomes for ex-prisoners have been rigorously evaluated. The aim of this study was to evaluate the impact of individualised case management on contact with health services during the first 6 months postrelease. Methods Single-blinded, randomised, controlled trial. Baseline assessment with N=1325 adult prisoners in Queensland, Australia, within 6 weeks of expected release; follow-up interviews 1, 3 and 6 months postrelease. The intervention consisted of provision of a personalised booklet ('Passport') at the time of release, plus up to four brief telephone contacts in the first 4 weeks post-release. Results Of 1179 eligible participants, 1003 (85%) completed =1 follow-up interview. In intention-to-treat analyses, 53% of the intervention group and 41% of the control group reported contacting a general practitioner (GP) at 1 month post-release (difference=12%, 95% CI 5% to 19%). Similar effects were observed for GP contact at 3 months (difference=9%, 95% CI 2% to 16%) and 6 months (difference=8%, 95% CI 1% to 15%), and for mental health (MH) service contact at 6 months post release (difference=8%, 95% CI 3% to 14%). Conclusions Individualised case management in the month after release from prison increases usage of primary care and MH services in adult ex-prisoners for at least 6 months post-release. Given the poor health profile of ex-prisoners, there remains an urgent need to develop and rigorously evaluate interventions to increase health service contact in this profoundly marginalised population. Trial registration number ACTRN12608000232336.